(untitled) (Journal of Dhaka Medical College, 2017)
Introduction: Abnormalities of serum testosterone level in males are observed in chronic kidney disease (CKD) patients. Erectile dysfunction, decreased libido, infertility in chronic kidney disease (CKD) patients is associated with low serum testosterone. So this study of CKD patients help early recognition of these adverse conditions associated with low serum testosterone level and thus specific actions may be taken earlier. Objective: To evaluate the serum testosterone level and the response of ADAM questionnaire in males with different stages of chronic kidney disease (CKD). Method: This cross sectional study was done From January to December, 2014 in the Department of Nephrology, Dhaka Medical College Hospital. A total of 90 diagnosed cases of adult male with different stages of CKD (CKD stage 3, 4, 5 and 5D) patients along with age matched 88 healthy individuals were included. Every subject was provided the Bangla version of ADAM questionnaire. Serum Testosterone was done by 125I-testosterone RIA system. P values <0.05 was considered as statistically significant. Result: Mean S. testosterone was found 4.29±1.9 ng/ml in CKD patients (group A) and 9.15±1.2 ng/ml in healthy subjects (group B). The mean S. Testosterone difference was statistically significant (p<0.05) between two groups. It was observed that positive response to ADAM questionnaire was found 11.4% in healthy subjects, 10.1% in CKD stage 3, 54.5% in CKD stage 4, 100% in CKD stage 5 and 5D. Among those groups only CKD stage 5 and 5D patients observed low S. testosterone and was found 39.1% and 84.0% respectively. Conclusion: Serum testosterone significantly decreased with progression of CKD stages. Positive ADAM questionnaire also found to be significant in CKD patients. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 73-78